On an extremal problem in the central limit theorems for sums of independent random variables - Zolotarev, V. M. (Lithuanian Mathematical Journal, 1964)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: В. М. Золотарев. Об одной экстремальной задаче в предельных теоремах для сумм независимых случайных величин V. M. Zolotariov. Apie vieną ribinių teoremų, nepriklausomų atsitiktinių dydžių sumoms, ekstremalinį uždavinį